Cardboard tubes as potential biodegradable potting containers: an explorative assessment - Tanesha; N. P Melkania; A. Arunachalam; Suresh Ramanan S (Indian Journal of Agroforestry, 2025)
The increasing environmental concerns associated with plastic waste in agriculture, particularly in seedling nurseries, necessitate the exploration of sustainable alternatives. This study investigates the use of biodegradable cardboard cylinder tubes as a substitute for traditional plastic pots in nurturing seedlings. The reliance on plastic pots contributes significantly to environmental pollution, with millions of seedlings requiring pots that ultimately end up in landfills or natural habitats. The Forest Advisory Committee in India has recognized this issue, advocating for the prohibition of polythene bags in afforestation projects to mitigate plastic waste. This research aims to quantify the decomposition rate of cardboard tubes under natural conditions and assess how environmental factors, such as rainfall and temperature, influence this process. Conducted at the ICAR-Central Agroforestry Research Institute in Jhansi, India, the study involved burying samples of varying sizes of cardboard tubes and monitoring their weight loss over time. Initial soil analyses were performed to evaluate nutrient release potential and its impact on seedling growth. Results indicate that cardboard tubes decompose effectively, with smaller sizes exhibiting faster degradation rates. The study found that temperature significantly affects decomposition, while rainfall had minimal impact. Additionally, the cardboard tubes provide an optimal environment for seed germination and minimize root disturbance during transplantation, enhancing overall plant health. This research underscores the potential of cardboard cylinder tubes as a viable eco-friendly alternative to plastic pots, contributing to sustainable agricultural practices and reducing plastic pollution. The findings highlight the importance of transitioning to biodegradable materials in horticulture to promote ecological balance and sustainability in large-scale planting initiatives